Development and Implementation of a Perianesthetic Safety Checklist in a Veterinary University Small Animal Teaching Hospital - Menoud, Gwennaëlle; Axiak Flammer, Shannon; Spadavecchia, Claudia; Raillard, Mathieu (Frontiers in Veterinary Science, 2018)
The use of a surgical safety checklist is recommended by the World Health Organization and is associated with advantages: improved communication and reduced complications and mortality. Adapting checklists to the environment in which they are used improves their efficiency, but their implementation can be challenging. The aim of this study was to develop and implement a perianesthetic safety checklist for a small animal hospital. Material and Methods: A panel of eight anesthesia diplomates and seven residents and doctoral students were gathered. The Delphi method was used to generate a checklist. The checklist was presented individually to each user by the primary investigator and introduced into the clinical routine over a 5-week period. An interdisciplinary meeting was then held, and the checklist was modified further. Six months after introduction, the use of the checklist was directly observed during 69 anesthetic cases and a survey was sent to the users. A second implementation was organized after formally presenting the checklist to the staff, designating the anesthesia clinical lead as the person responsible for printing and controlling use of the checklist. A second evaluation was performed 3 months later (64 anesthetic cases). Results: Using the Delphi process led to the creation of a checklist consisting of three parts: "sign in" (before induction of anesthesia), "time out" (before the beginning of the procedure), "sign out" (at the end of the procedure). At the first assessment, the checklist was printed and used in 32% of cases and not printed in 41% of cases. Response rate of the survey was fair (19/32 surveys): 14/19 users thought the checklist contributed to improving communication; 15/19 reported improved safety and better management of the animals; 9/19 users avoided mistakes (77% would have omitted the administration of antimicrobial prophylaxis); 10/19 thought it was time consuming. At the second assessment, the checklist was used in 45% of cases (printed but not used in 55%). The use of the sign-out section of the checklist was significantly improved. Conclusions and clinical relevance: This study illustrates an innovative use of the Delphi method to create a safety checklist. Challenges associated with implementation are reported.